Open J Environ Biol 2017
DOI: 10.17352/ojeb.000003
|View full text |Cite
|
Sign up to set email alerts
|

Metal (Loid)s in Farmland Soils and Strategies to Reduce Bioavailability

Abstract: High concentrations of heavy metal (loid)s (HMs) in farmland soils reduces crop yield and contaminates the food chain. Exposure to HMs in the diet results in several adverse health effects such as cancer, reproductive health problems and cardiovascular diseases. Understanding the origin and fractionation of these toxic substances will provide direction for reducing their bioavailability in contaminated farmland soils. HMs are added to farmland soils through activities such as irrigation, organic and inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 182 publications
(187 reference statements)
2
2
0
Order By: Relevance
“…Table 4 indicates that, V occurred mostly as oxides of Fe and Mn in the studied soils in the dry and rainy seasons. This is similar to the results obtained by Agnieszka and Barbara (2012) and Fayiga and Nwoke (2017). The separation of V into the various soil fractions varied as follows: Red > Aex > Ox > Res.…”
Section: Speciation Of Trace Metals In the Studied Soils And Controlsupporting
confidence: 89%
“…Table 4 indicates that, V occurred mostly as oxides of Fe and Mn in the studied soils in the dry and rainy seasons. This is similar to the results obtained by Agnieszka and Barbara (2012) and Fayiga and Nwoke (2017). The separation of V into the various soil fractions varied as follows: Red > Aex > Ox > Res.…”
Section: Speciation Of Trace Metals In the Studied Soils And Controlsupporting
confidence: 89%
“…The concentrations of As observed in Malawian medicinal herbs in this study were compared to those reported in medicinal herbs from other African countries. For Moringa oleifera , the results revealed that the mean As concentration obtained in this study (range: 0.048–0.078 mg kg −1 ) fell within the range reported in Ghana (0.06–2.04 mg kg −1 ) [33] , but it was significantly lower than that from Nigeria (range: 0.17–1.21 mg kg −1 ) [2] , [27] , [34] , Ethiopia (range: 0.24–1.11 mg kg −1 ) [2] , [35] , [36] and Uganda (range: 0.29–0.99 mg kg −1 ) [2] , [28] . It is important to note that the US Food and Drug Administration (FDA) has established a maximum contaminant level (MCL) of 3.00 mg kg −1 for As in herbs and spices [37] .…”
Section: Resultssupporting
confidence: 60%
“…It was recorded that the ash-sewage sludge mixture can substantially enhance soil fertility, increase plant biomass and uptake of potassium and magnesium. However, even stabilised and aged BS are often (over)loaded with a range of persistent toxic (i) inorganic (metals/metalloids, metallic nanoparticles) 62 and (ii) emergent organic (furans, halogens, nonylphenols and nonylphenol ethoxylates, polyaromatic hydrocarbons, linear alkylbenzenesulfonates polychlorinated biphenyls, polychlorinated dibenzo- p -dioxins) contaminants, 44 hardly to be immobilised or removed from the BS matrix.…”
Section: Biosolids (Bs): Resources Of Nutrients and Organicsmentioning
confidence: 99%